The Dependence of Northwest Pacific Tropical Cyclone Intensification Rates on Environmental Factors - Xinyan Lyu; Xuguang Wang; Lance M. Leslie (Advances in Meteorology)
The Northwest Pacific tropical cyclone (TC) intensification is classified into rapid intensification (RI), normal intensification (NI), and slow intensification (SI) categories. The initial location and intensity, the preceding intensity change, the motion direction, the occurrence month, and the intensification duration time are all found to differ for RI cases compared with NI and SI cases. The dependence of RI, NI, and SI on environmental conditions is further examined statistically by using the intensification rates of named TCs, for the 21-year period 1995–2015, obtained from JTWC best track data, and the environmental conditions derived from the ERA-Interim reanalysis data and GODAS high-resolution global ocean analysis data. It was found that deep-layer and upper-mid vertical wind shear (VWS), upper-level outflow, sea surface temperature (SST), and ocean heat content (OHC) are statistically different among RI, NI, and SI both before and during intensification. RI is enhanced by weaker and decreasing VWS, warmer oceans, and stronger and increasing outflow. In contrast, SI typically occurs with larger and increasing VWS, cooler oceans, and weaker, static outflow. The impacts of low-level VWS and net moisture inflow are only significantly different between RI and SI and between NI and SI, but not between RI and NI. Another key finding is that increased upper-level outflow and decreased VWS are important precursors and hence are possible predictors, of RI onset. The direction of upper-level outflow affects TC intensification, with NW and NE outflow being more favorable for TC RI than SE and SW outflow.